Linguistic analysis of the newspaper discourse in Brazil: the older people and COVID-19 - Dias de Castilho Ehrler, Thais; Große, Sybille (HCIAS working papers on Ibero-America, 2022)
Brazil has been one of the countries most affected the COVID-19 pandemic. The measures taken by the Brazilian government to contain the spread of the virus have been the subject of national and international criticism. Among these measures is the topic of protection and isolation ofolder adults, which has been subject of discussion in Germany. Based on a discourse led by analytical and linguistic approach this paper analyses the media and public perception of the older generation concerning the coronavirus. Using both quantitative and qualitative methods of corpus analysis, we investigate the question of whether the older people are associated with the COVID-19 virus in a particular form and whether they are exposed to specific discrimination as a population group. The results of the data gathered from March to July 2020 show that older adults are often described as being vulnerable and belonging to the risk group in Brazilian media.
Gesehen am 08.03.2022